Influence of Strong Acid Hydrolysis Processing on the Thermal Stability and Crystallinity of Cellulose Isolated from Wheat Straw - Chemar J. Huntley; Kristy D. Crews; Mohamed A. Abdalla; Albert E. Russell; Michael L. Curry (International Journal of Chemical Engineering)
Cellulose extractions from wheat straw via hydrochloric, nitric, and sulfuric acid hydrolysis methods were carried out. X-ray diffraction spectral analyses reveal that depending on the acid conditions used the structure of the cellulose exhibited a mixture of polymorphs (i.e., CI and CIII cellulose phases). In addition, the percent crystallinity, diameter, and length of the cellulose fibers varied tremendously as determined by X-ray diffraction and scanning electron microscopy. Thermal gravimetric analysis measurements revealed that the thermal stability of the extracted cellulose varied as a function of the acid strength and conditions used. Scanning electron microscopy analysis revealed that the aggregation of cellulose fibers during the drying process is strongly dependent upon the drying process and strength of the acids used.